PENERAPAN DIAPHRAGMATIC BREATHING EXERCISE PADA GANGGUAN GERAK DAN FUNGSI SENDI LUMBAL PADA KONDISI NON-SPECIFIC LOW BACK PAIN - Dwi Herdayanti (Masker Medika, 2024)
Introduction: Low Back Pain (LBP) is a form of disorder in the structure of the back muscles that generally occurs due to trauma. LBP can cause pain, muscle spasms and muscle imbalances, so that the stability of the abdominal and lower back muscles decreases, lumbar mobility is limited, resulting in a decrease in functional activity. Purpose: To determine the effect of Diaphragmatic Breathing Exercise intervention on Lumbar Joint Movement and Function Disorders in Non-Specific Low Back Pain Conditions. Methods: This study uses a quantitative approach, the method used in this study is a quasi-experiment with a one-group pre-test design. The research period was carried out from December 2023 to June 2024. Data collection was carried out using the Oswestry Disability Index (ODI) questionnaire. The number of samples in this study was 17 respondents using the purposive sampling technique. Results: In the hypothesis test, the value of p = 0.040 (p < 0.05) was obtained, which means that Ho is accepted and means that there is an effect of Diaphragmatic Breathing Exercise intervention on Lumbar Joint Movement and Function Disorders in Non-Specific Low Back Pain Conditions. Discussion: Diaphragmatic Breathing Exercise physiotherapy intervention can be done in an easy, short time and has a good effect on impaired movement and lumbar function in non-specific low back pain. Keywords: Non-Specific Low Back Pain, Diaphragmatic Breathing Exercise.